Clinico-aetiological profile and outcome in children with acute febrile encephalopathy - Singh, Divya; Bamnawat, Subhash (International Journal of Contemporary Pediatrics, 2022)
Background: Acute febrile encephalopathy (AFE) is a medical emergency as well as diagnostic and therapeutic challenge in children. Objective of this study was to assess clinico-aetiological profile and outcome in children with AFE. Methods: This prospective observational study was carried out at tertiary care hospital Udaipur, from January 2020 to July 2021. Total 61 children aged 1 month to 18 years who were admitted in PICU with fever ≤2 weeks duration and altered sensorium either at onset or following fever were enrolled. Patient’s detailed history and physical examination including detailed neurological examinations were recorded on pre-structured performa. The investigations included CBC with PBF, ESR, malarial parasite, dengue, scrub typhus, typhi-dot, blood sugar, KFT, electrolytes, LFT, calcium, CSF examination, urine examination, X-ray chest. ABG, serum ammonia, blood culture for bacteriological studies and CT/MRI brain were performed whenever required. Results: 61 patients were admitted with fever and loss of sensorium. The most common clinical sign was the pallor (63.9%) and vomiting (55.7%) was the most common clinical symptom. Cerebral malaria was the commonest cause (31.1%) of AFE followed by suspected viral encephalitis (14.7%) and pyogenic meningitis 9 (14.7%). Out of total 61 patients, 45 (73.8%) patients were discharged and 16 (26.2%) patients were expired. Maximum mortalities were seen in Reye’s syndrome (5 out of 6 cases) and was most in age group <5 years of age (26 cases). Conclusions: Cerebral malaria was the leading cause of AFE followed by suspected viral encephalitis and pyogenic meningitis. While determining the aetiology of AFE in a malarial endemic area, cerebral malaria should be considered in all patients. Reye’s syndrome should also be considered in patients of AFE should be evaluated to diagnose or rule out this entity.